DEVELOPMENT OF ETHNOMATHEMATICS-BASED NUMERACY LITERACY TASKS USING PACU JALUR LOPEK TRADITION CONTEXT FOR ELEMENTARY STUDENTS - Lara Oktarisa; Zetra Hainul Putra; Erlisnawati Erlisnawati; Muhammad Fendrik (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Mathematics is a subject that must be taught at every level of education, including elementary school. However, many students find it difficult because it is abstract and lacks connection to everyday life. In addition, students' low numeracy literacy is also a factor that hinders their understanding of mathematical concepts. Based on observations at SDN 026 Pulau Banjar Kari, it was found that students have difficulty in solving numeracy problems that require analysis and problem solving skills. Therefore, this study aims to develop ethnomathematics-based numeracy literacy questions on the pacu jalur lopek tradition for phase B elementary school students. This research used the Research and Development (R&D) method with the 4D development model, namely define, design, develop, and disseminate. The developed questions were tested on a small scale (4 students) and a wide scale (35 students). Data analysis used Aiken V and Rasch Model. The results of expert validation showed a value of 0.910 (very valid), while student trials resulted in 22 valid questions out of 24 questions with a reliability of 0.79 (good category). Thus, this ethnomathematics-based numeracy literacy question meets the valid and reliable criteria for phase B primary school students